Procedure and practice of the Royal Chancery of Valladolid. The distribution of lawsuits to notaries - Marcos Díez, David (Cuadernos de Historia del Derecho, 2025)
The apportioner of lawsuits of the Royal Chancery of Valladolid was the official who, from an early date, guaranteed equality and balance in the activities of the court clerks of the Castilian High Court, as well as the proper conduct of litigation in its initial phase. This article examines the regulations that gave rise to the office and the apportionment procedure, as well as analyzes the office itself, its holders and the procedure itself; highlighting its influence on other Spanish and American high courts, as well as on the apportionment of judicial matters in the contemporary administration of justice.